Cerebral paragonimiasis: Clinicoradiological features and serodiagnosis using recombinant yolk ferritin. - Jeong-Geun Kim (PLoS Neglected Tropical Diseases, 2022)
Cerebral paragonimiasis (CP), caused by aberrant migration of Paragonimus worms, frequently invokes serious illness. The causal relationship between the lesion characteristics and patients' symptoms has poorly been understood. CP serodiagnosis has not been properly evaluated to date. A total of 111 CP cases were diagnosed in our laboratory between 1982 and 2003. This study retrospectively assessed the clinical and imaging characteristics of the 105 patients along with the evaluation of diagnostic potentials of recombinant P. westermani yolk ferritin (rPwYF) by enzyme-linked immunosorbent assay (ELISA) employing patients' sera and cerebrospinal fluids (CSFs). We analyzed 60 male and 45 female patients; 50 early-stage patients with non-calcified enhancing nodule(s) (median age, 38 years; interquartile range [IQR], 24.75-52; median symptom duration, 0.75 years; IQR, 0.2-2) and 54 chronic cases having calcified lesion(s) (median age, 33 years; IQR, 25-41; median symptom duration, 10 years; IQR, 5-20). One patient showed a normal neuroimage. The patients were largely diagnosed in their 30s. The parietal lobe was most commonly affected, followed by occipital, frontal, and temporal lobes. Twenty-six patients had lesions encompassing ≥ two lobes. The patients complained mainly of seizures, headaches, hemiparesis, and focal neurologic deficits (P < 0.001). Seizures and visual defects were predominant in patients with calcified lesion(s) (P < 0.001). The diagnostic sensitivity and specificity of rPwYF against serum/CSF were 100%/97% and 97.2%/92.5%, respectively. The specific IgG antibody levels against rPwYF in sera and CSFs showed a positive correlation (r = 0.59). The clinical manifestations of the early-stage patients might be associated with cortical lesions or meningeal irritation, while those in the chronic stage were caused by conglomerated space-occupying lesions. rPwYF would be useful for the serodiagnosis of both early and chronic CP cases.